(untitled) (Jurnal Destinasi Pariwisata, 2025)
Badung Regency in Bali is a major tourist destination facing increasing traffic congestion that affects accessibility and visitor satisfaction. This research aims to analyze the planning process of the Bali subway project and evaluate its potential to improve tourism quality. A qualitative approach was used, with data collected through in-depth interviews involving stakeholders such as the Department of Transportation, Department of Tourism, PT SBDJ, local communities, and tourists. The study applied the UNWTO’s eight tourism quality indicators as an analytical framework. The findings indicate that the Bali subway development serves as a strategic response to transportation challenges by enhancing accessibility, safety, and comfort for tourists. It also integrates principles of sustainable development and respects local cultural values such as Tri Hita Karana. The project is expected to reduce reliance on private vehicles and improve the overall travel experience, supporting long-term destination competitiveness. In conclusion, the Bali subway is not merely a transportation project but a strategic investment in tourism infrastructure. Its success depends on continuous evaluation, government commitment, and effective integration with existing transport systems to ensure relevance to both visitors and local communities.